Robinsoniella peoriensis Infections in Humans-A Narrative Review - Petros Ioannou; Stella Baliou; Diamantis Kofteridis (MDPI AG, 2024)
Robinsoniella peoriensis is a Gram-positive, strictly anaerobic, spore-forming, rod-shaped bacterium belonging to the phylum Firmicutes and the family Lachnospiraceae. Until now, R. peoriensis is the only species of its genus. It was first isolated in 2003 during a study into the flora of lagoons and manure pits. Given the rarity of this microorganism and the sparse information in the literature about its way of transmission, the way to diagnose its infections and identify it in the microbiology laboratory, and its public health relevance, the present study aimed to identify all the published cases of Robinsoniella, describe the epidemiological, clinical, and microbiological characteristics, and provide information about its antimicrobial resistance, treatment, and outcomes. A narrative review was performed based on a Pubmed/Medline and Scopus databases search. In total, 14 studies provided data on 17 patients with infections by Robinsoniella. The median age of patients was 63 years and 47% were male. The most common types of infection were bone and joint infections, bacteremia, infective endocarditis, and peritonitis. The only isolated species was R. peoriensis, and antimicrobial resistance to clindamycin was 50%, but was 0% to the combination of piperacillin with tazobactam, aminopenicillin with a beta-lactamase inhibitor, and metronidazole which were the most commonly used antimicrobials for the treatment of these infections. The overall mortality depends on the type of infection and is notable only for bacteremia, while all other infections had an optimal outcome. Future studies should better assess these infections' clinical and epidemiological characteristics and the mechanisms of the antimicrobial resistance of this microorganism from a mechanistic and genetic perspective.